Expanding Language Development Among Children And Communication Disorders - Nur Hayati Yusuf; Pingkan Titania Patmawati (Universitas Muhammadiyah Surabaya, 2020)
Abstract : Language development disorder is the inability or limitations in using linguisticsymbols to communicate verbally or delays in children's speech and language development abilities according to their age group, gender, customs and intelligence. Therefore, if speech and base disorders are not treated properly, there will be impaired reading ability, verbal ability, behavior, psychosocial adjustment, and poor academic ability. Parents or teachers need to understand this problematic behavior because